Infective endocarditis caused by Streptococcus gallolyticus subspecies pasteurianus and colon cancer - Takamura, Noriko (BMJ Publishing Group, 2014)
A 56-year-old man presented to our department with a 2-month history of fever and chills. He had received a mitral valvuloplasty 3 years ago. He had been administered levofloxacin for 2 months. We discontinued levofloxacin and repeated the blood cultures. Bacterial blood cultures were positive and transoesophageal echocardiography revealed vegetation attached to the posterior mitral leaflet. We started the patient on intravenous antibiotic therapy for infectious endocarditis by Streptococcus gallolyticus subspecies pasteurianus. A colonoscopic screening revealed adenomatoid intracellular carcinoma. Previous studies have reported a weak association between colorectal cancer and Streptococcus bovis biotype II/2, which includes S gallolyticus subspecies pasteurianus; however, the rate is notably higher than the rate of colorectal cancer as indicated by positive faecal occult-blood test results. We conclude that colonoscopies should be routine while scanning for colorectal cancer in all patients with S bovis bacteraemia, regardless of the subspecies.